Estimating Time Since Death: A Forward Chaining-Based Expert System Design - D.Noveriyanti; E.E Surbakti; R. Winantyo (International Journal of Integrated Engineering, 2026)
The death rate in Indonesia continues to rise each year. Forensic specialists play a crucial role in estimating the time since death by examining the condition of the body. Their responsibilities extend beyond body examinations to various other cases involving biological evidence. However, the increasing death rate and the complexity of cases often exceed the number of dedicated forensic specialists in the country. To address this challenge, advancements in technology can enhance the effectiveness of forensic specialists. An expert system utilizing the forward chaining method has been developed to estimate the time interval since death. This system aims to assist forensic professionals and the courts in determining the time of death more accurately. The estimation system was designed with an inference engine that incorporates 33 characteristics of corpses and categorizes them into 12 intervals of time since death. It produces output that is aligned with predefined rules. The system achieved 100% accuracy when tested with 30 expert-validated corpse cases.